How to fight inequality : (and why that fight needs you) - Phillips, Ben (Civil society activist) (Medford : Polity, 2020)
'A DIY-guide to tackling inequality for activists everywhere'--
Includes bibliographical references and index.
Keywords: Equality; Income distribution; Elite (Social sciences) -- History -- 21st century; Social policy